Carnitine Requires Choline to Exert Physiological Effects in Saccharomyces cerevisiae - du Plessis, Michelle; Franken, Jaco; Bauer, Florian F. (Frontiers in Microbiology, 2018)
L-Carnitine is a key metabolite in the energy metabolism of eukaryotic cells, functioning as a shuttling molecule for activated acyl-residues between cellular compartments. In higher eukaryotes this function is essential, and defects in carnitine metabolism has severe effects on fatty acid and carbon metabolism. Carnitine supplementation has been associated with an array of mostly beneficial impacts in higher eukaryotic cells, including stress protection and regulation of redox metabolism in diseased cells. Some of these phenotypes have no obvious link to the carnitine shuttle, and suggest that carnitine has as yet unknown shuttle-independent functions. The existence of shuttle-independent functions has also been suggested in Saccharomyces cerevisiae, including a beneficial effect during hydrogen peroxide stress and a detrimental impact when carnitine is co-supplemented with the reducing agent dithiothreitol (DTT). Here we used these two distinct yeast phenotypes to screen for potential genetic factors that suppress the shuttle independent physiological effects of carnitine. Two deletion strains, Δcho2 and Δopi3, coding for enzymes that catalyse the sequential conversion of phosphatidylethanolamine to phosphatidylcholine were identified for suppressing the phenotypic effects of carnitine. Additional characterisation indicated that the suppression cannot be explained by differences in phospholipid homeostasis. The phenotypes could be reinstated by addition of extracellular choline, but show that the requirement for choline is not based on some overlapping function or the structural similarities of the two molecules. This is the first study to suggest a molecular link between a specific metabolite and carnitine-dependent, but shuttle-independent phenotypes in eukaryotes.